2016
DOI: 10.18006/2016.4(5).557.563
|View full text |Cite
|
Sign up to set email alerts
|

Improving date palm (phoenix dactylifera l. cv. estamaran) calogenesis by the use of zinc oxide nanoparticles

Abstract: To study the effects of zinc nanoparticles on date palm cv. Estamaran (Sayer) callus induction under in vitro condition, a research with two separate experiments was conducted using a completely randomized design. In the first experiment, MS basal salt medium containing 100 mg/l 2,4-D, 3 mg/l 2ip, 3 g/l activated charcoal, 30 g/l sucrose, 40 mg/l adenine sulfate, and 1 mg/l biotin along with different concentrations of zinc sulfate (ZnSO4), including 0, 2.43, 4.86 mg/l or zinc oxide nanoparticles (ZnO NPs), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The fruits of date palm were affected by the treatment with nano-fertilizers and this is consistent with many studies on date palm (Amiri et al 2016;Roshdy and Refaai 2016;Altemimy et al 2019;Ahmed 2019a, 2019b). The ripening rate was reduced due to the slow growth of fruit, continued accumulation of metabolites, high levels of IAA and gibberellins, low activity of enzymes such as POD and SOD (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fruits of date palm were affected by the treatment with nano-fertilizers and this is consistent with many studies on date palm (Amiri et al 2016;Roshdy and Refaai 2016;Altemimy et al 2019;Ahmed 2019a, 2019b). The ripening rate was reduced due to the slow growth of fruit, continued accumulation of metabolites, high levels of IAA and gibberellins, low activity of enzymes such as POD and SOD (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have recently been done on the effect of foliar nano-fertilizer on date palm production (Amiri et al 2016;Roshdy and Refaai 2016;Altemimy et al 2019;Ahmed 2019a, 2019b). Also, Roshdy and Refaai (2016) found that soil-applied nano-fertilizer improved the growth and production of date palm compared with the use of traditional fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of 10mg L -1 of nano silver + nano zinc treatment was superior in recording the highest rate for P% in leaves. Results in Table (7) cleared that leaf content of K significantly increased by adding nano silver nitrate to culture medium compared with the control. Also, it could be observed that, cultured which grow in media supplemented with nano zinc achieved significant increasing in shoots content of potassium.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, zinc is essential for producing chlorophyll and starch by effects on the enzymes of their formation (06). Many studies have shown that zinc can significantly improve plant growth in vitro, including Brassica nigra (33), Phoenix dactylifera (7), Coffea arabica (13) and Musa acuminata (26). Moreover, Alharby et al,(1) found that 15mg.L -1 of nano zinc increased tomato callus growth and multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of engineered NPs (ENPs) on plants varied according to the composition, concentration, and size, as well as physical and chemical properties of ENPs (Ma et al 2010). Accumulative evidence suggests that ZnO NPs can enhance the growth and development in many plants, including the callus of date palm (Prasad et al, 2012;Amiri et al, 2016). Our results showed that ZnO NPs at 150 mg L −1 have a positive effect on date palm growth, including the accumulation of carbohydrates, total soluble proteins and free amino acids.…”
Section: Discussionmentioning
confidence: 99%